Influence of self determination factors and green human resource management practices on employee retention among hotel employees in Nigeria - Emmanuel, Adeyefa Adedayo (2021)
Organisations currently seek optimal approaches to mitigate turnover rates and increase employee retention (ER) for various organisational possibilities. Specifically, retention denotes positive organisational credibility, simplified recruitment processes, and improved productivity and incomes. Green Human Resource Management (GHRM) substantially impacts HRM sustainability in bridging the organisational image-sustainable environmental goal gap. Several concerns have been associated with the key determinants of hotel turnover in Nigeria. For example, employees were not intrinsically motivated with many individuals unable to perform optimally, inadequately trained, and lacking employer-employee rapport. Past studies also emphasised the individual and contextual indicators of employee self-development rather than environmental sustainability given its relative novelty in the Nigerian tourism and hospitality industry. This study aims to determine the impacts of SD variables (green personal value or GPV, green self-efficacy or GSE, and employee green behaviour or EGB), GHRM policies (green recruitment and selection or GRS, green training and development or GTD, green performance and appraisal or GPA, green pay and reward or GPR, employee green relations or EGR, and green health and safety or GHS) that affected ER among the hotel employees in Nigeria with empowerment as a mediator given the research paucity involving the self-determination (SD) effect on employee retention [specifically regarding green practices through the self-determination theory (SDT)]. Meanwhile, the Organisational Support Theory (OST) and Self-Determination Theory (SDT) highlighted the underpinning research theories with a quantitative research paradigm under the correlation study methodology. A total of 430 respondents encompassing operational-level staff in seven Nigerian green practice hotels addressed the structured questionnaire. Two statistical software were employed to analyse the collected data: (i) Statistical Package for the Social Science Window Software 23 and (ii) Structural Equation Modelling (SEM) with Smart Partial Least Square (PLS) 3.0. Resultantly, GPV and EGB proved significant in increasing staff retention among hotel employees in Nigeria. The GTD, GHS, EGR, and employee empowerment (EE) also improved ER among hotel employees in Nigeria. Conversely, GRS, GPA, GPR, and GSE proved insignificant in enhancing ER among hotel employees in Nigeria. Hence, GHRM substantially impacted employee retention in Nigeria with positive correlation values between most variables and retention in the study outcomes. This research expanded the current body of knowledge on ER with OST and SDT in green practice or environmental issue contexts among hotel employees in Nigeria following the (i) inadequate procedures implemented among the Nigerian hotel management and (ii) lack of theoretical growth perspectives. The study also contributed knowledge and guidelines to employers on the GHRM practice effects on hotel ER with relevant implementations. Lastly, potential (particularly cross-sectional) studies are encouraged to compare staff performance between non-green and green hotels across developing countries.